Stem Distributions and Incremental Values of Selected Dipterocarp and Non-Dipterocarp Species Within the 50-Hectare Plot of the Pasoh Forest Reserve, Negeri Sembilan, Peninsular Malaysia - Galante, Michael Victor (2002)
The objective of this study is to comparatively evaluate the distribution and growth increments of selected Dipterocarp and Non-Dipterocarp species occurring in the natural forest area of the 50-ha Plot, Pasoh Forest Reserve, Negeri Sembilan. The trees selected from the Dipterocarpaceae family are: Shorea leprosula Miq., Shorea macroptera Dyer., and Shorea parvifolia Dyer., and the trees from the Non- Dipterocarpaceae family are: Cynometra malaccensis Meewen. (Leguminoseae family), Koompassia malaccensis Benth. (Leguminoseae), and Quercus argentata Korth. (Fagaceae family). For each of these species within the years 1987, 1990, and 1995, the calculation of the stand density, periodic mean annual diameter increment, average annual basal area increment, mortality, and volume was conducted. Data enhancement by plotting the spatial distributions and conducting tests for correlation (linear regression) were conducted for precision. The results showed that the stand density of Shorea leprosula Miq., Shorea macroptera Dyer., Shorea parvifolia Dyer., Cynometra malaccensis Meewen., Koompassia malaccensis Benth. and Quercus argentata Korth., for all trees > 1 cm dbh in the 50-ha plot averaged 2643.67 ha-1, 1555.33 ha-1, 1469.33 ha-1, 1192 .33 ha-1, 6 54.33 ha-J, and 981 trees ha-J respectively.